Methylation in benign prostate and risk of disease progression in men subsequently diagnosed with prostate cancer. Issue 12 (2nd March 2016) - Rybicki, Benjamin A.; Rundle, Andrew; Kryvenko, Oleksandr N.; Mitrache, Nicoleta; Do, Kieu C.; Jankowski, Michelle; Chitale, Dhananjay A.; Trudeau, Sheri; Belinsky, Steven A.; Tang, Deliang
Abstract : In DNA from prostate tumors, methylation patterns in gene promoter regions can be a biomarker for disease progression. It remains unclear whether methylation patterns in benign prostate tissue—prior to malignant transformation—may provide similar prognostic information. To determine whether early methylation events predict prostate cancer outcomes, we evaluated histologically benign prostate specimens from 353 men who eventually developed prostate cancer and received "definitive" treatment [radical prostatectomy (58%) or radiation therapy (42%)]. Cases were drawn from a large hospital‐based cohort of men with benign prostate biopsy specimens collected between 1990 and 2002. Risk of disease progression associated with methylation was estimated using time‐to‐event analyses. Average follow‐up was over 5 years; biochemical recurrence (BCR) occurred in 91 cases (26%). In White men, methylation of the APC gene was associated with increased risk of BCR, even after adjusting for standard clinical risk factors for prostate cancer progression (adjusted hazard ratio (aHR) = 2.26; 95%CI 1.23–4.16). APC methylation was most strongly associated with a significant increased risk of BCR in White men with low prostate specific antigen at cohort entry (HR = 3.66; 95%CI 1.51–8.85). In additional stratified analyses, we found that methylation of the RARB gene significantly increased risk of BCR in African American cases who demonstrated methylation of at least one of the other four genes under study (HR = 3.80; 95%CI 1.07–13.53). These findings may have implications in the early identification of aggressive prostate cancer as well as reducing unnecessary medical procedures and emotional distress for men who present with markers of indolent disease. Abstract : What's new? Methylation patterns hold clues to the risk of disease progression in men with prostate cancer. Whether risk of malignant transformation from benign prostatic disease can be similarly deduced is unknown. Here, methylation patterns in gene promoter regions were analyzed in benign tissue samples collected from men who later developed prostate cancer. In white men only, methylation of a known tumor suppressor gene in premalignant benign prostate was associated with an increased risk for subsequent disease progression. The results suggest that race‐specific methylation panels could play a role in the early detection of aggressive prostate cancer.